The importance of EN ISO 15189 accreditation of allergen‐specific IgE determination for reliable in vitro allergy diagnosis. Issue 2 (February 2015) - Lambert, C.; Sarrat, A.; Bienvenu, F.; Brabant, S.; Nicaise‐Roland, P.; Alyanakian, M.‐A.; Apoil, P.‐A.; Capron, C.; Couderc, R.; Evrard, B.; Jaby, D.; Hémont, C.; et al.
Abstract Background Allergen‐specific serum immunoglobulin E detection and quantification have become an important step in allergy diagnosis and follow‐up. In line with the current trend of laboratory test accreditation to international standards, we set out to design and assess an accreditation procedure for allergen‐specific serum IgE. Methods Method validation according to the accreditation procedure under the EN ISO 15189 standard was carried out for allergen‐specific immunoglobulin E determination using the fluoroimmunoenzymatic method ImmunoCAP® (ThermoFisher). Data were produced by 25 hospital laboratories in France. A total of 29 allergen specificities including mixes, extracts, and molecular allergens were assayed. Allergen‐specific serum immunoglobulin E concentrations ranged from 0.1 to 100 kUA/l. Results Repeatability, reproducibility, and accuracy results fulfilled method validation criteria for automated laboratory tests and proved similar irrespective of the allergen specificity, allergen‐specific serum immunoglobulin E concentration, or individual laboratory. Conclusion Allergen‐specific serum immunoglobulin E determination with the fluoroimmunoenzymatic method ImmunoCAP® is a highly repeatable, reproducible, and accurate method which may be considered as a single analyte assay in view of the EN ISO 15189 accreditation procedure.